IMPROVEMENT OF WORK METHODS BASED ON MICROMOTION STUDY TO INCREASE TECHNICAL PRODUCTIVITY (Case Study at Nissan Ahmad Yani Surabaya Workshop): IMPROVEMENT OF WORK METHODS BASED ON MICROMOTION STUDY TO INCREASE TECHNICAL PRODUCTIVITY (Case Study at Nissan Ahmad Yani Surabaya Workshop) - Nurcahyanie, Yunia Dwie (UNIPA PRESS, 2018)
In the world of automotive innovation is not just about products, but services are also not less important always to be developed. Especially as it is today, people tend to like fast service but does not neglect the quality of the services provided. In this study using Micromotion Study, where technicians will be recorded every movement while using the old method of doing improvements to then be processed in order to generate new working methods that are more effective and efficient. Data retrieval is done by as much as 30 times on each experiment that is using the old methods and the new methods being used, the technicians then processed using computer software be Paired T-Test then the average productivity for the old method was 38.03 seconds/unit. Whereas with the new method have average 25.47 minutes/units, so that an increase in as much as 12.27 min/units or of 32.24%. With productivity increases, then the unit enters the vehicle servicing technicians are carried out can also be increased. So a new method that is already done in the workshop workable Nissan Ahmad Yani Surabaya to further accelerate the servicing work, and can increase the unit entry service.